Território e participação política : o colegiado territorial norte fluminense - Lopes, Jonathan Felix Ribeiro (2012)
This dissertation aims to identify ways in which the implementation of the Territorial Board Norte Fluminense, provided experiences of political participation in territorial scope. For this, we tought an interdisciplinary understanding of political participation. Moreover, empirical research sought to identify, through analysis of official documents of theTerritories of Citizenship Program, questionnaires and interviews which the impact of policy on political participation in the area studied. Institutional advances were perceived at the same time the persistence of authoritarian traits in the actions of the Brazilian state.